Inflammatory ringworm due to Microsporum audouinii, case of a severe form in an immunocompetent girl in Mauritania - SY Ousmane; Ba Ousmane; Mamadou D. Ball (IDCases, 2023)
Introduction: Ringworms of the scalp are very commons in Mauritania and among them; inflammatory ringworms are representing very rare forms. We present the case of a severe inflammatory ringworm caused by an anthropophilic dermatophyte, Microsporum audouini. Observation: This is an 8-years-old girl with ulcerative lesions on the scalp without adenopathy, without fever and in a good general condition. Direct examination of the mycological sample of hair and scales showed the presence of ecto-trix spores. Culture in SCA media allowed the identification of Microsporum audouini. The establishment of an antifungal treatment orally and a local antiseptic allowed to have a clinical and mycological remission after 30 days. Conclusion: Microsporum audouinii is most often responsible for very soft trichophytia, but under certain conditions, it can cause inflammatory ringworm.